2004
DOI: 10.1007/s00213-004-1825-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low doses of ?9-tetrahydrocannabinol and cannabidiol on the extinction of cocaine-induced and amphetamine-induced conditioned place preference learning in rats

Abstract: These results are the first to show that both delta9-THC, which acts on both CB 1 and CB2 receptors, and CBD, which does not bind to CB1 or CB2 receptors, potentiate the extinction of conditioned incentive learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
125
2
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(149 citation statements)
references
References 36 publications
17
125
2
4
Order By: Relevance
“…Alone, CBD, a cannabinoid void of THC-like psychoactivity, produced no preference or aversion at any of the four doses tested. These results are consistent with a previous report in which 5 mg/kg CBD alone failed to alter preference in a place conditioning procedure in rats (Parker et al, 2004). However, in that study both CBD and THC potentiated cocaine and amphetamine induced extinction of place preference learning.…”
Section: Place Conditioning Effects Of Thc and Cbdsupporting
confidence: 93%
“…Alone, CBD, a cannabinoid void of THC-like psychoactivity, produced no preference or aversion at any of the four doses tested. These results are consistent with a previous report in which 5 mg/kg CBD alone failed to alter preference in a place conditioning procedure in rats (Parker et al, 2004). However, in that study both CBD and THC potentiated cocaine and amphetamine induced extinction of place preference learning.…”
Section: Place Conditioning Effects Of Thc and Cbdsupporting
confidence: 93%
“…The design of the present experiments cannot discriminate between these two potential mechanisms; however, a memory deficit explanation is less tenable in light of the finding in experiment 1 that the highest dose of CBD (10 mg/kg) did not modify the expression of gaping. Furthermore, at a dose of 5 mg/kg CBD neither affected the acquisition nor retrieval of a floor-amphetamine association in a conditioned place preference task (Parker et al 2004a) or of a flavor-lithium association in a conditioned taste avoidance task (Parker et al 2002). Finally, Varvel et al (2007) reported that mice pre-treated with the FAAH inhibitor, OL-135, as well as FAAH knockout mice with elevated central AEA levels, did not display memory impairment or motor disruption in a spatial memory task (Morris water maze); in fact, the FAAH knockouts displayed a significant increase in acquisition rate.…”
Section: Discussionmentioning
confidence: 84%
“…This is in keeping with similar indications observed in rats in which cannabidiol reversed apomorphine-induced stereotypy (Zuardi et al, 1991) and in a female schizophrenic patient in whom cannabidiol markedly reduced psychotic symptoms (Zuardi et al, 1995). The dose range of cannabidiol (1, 5, and 15 mg/kg) used in the present study is lower than doses previously determined to reverse the effects of psychoactive drugs in rats (Zuardi et al, 1991;Moreira and Guimaraes, 2005); however, it has previously been shown to be active in extinguishing conditioned place preference learning induced by amphetamine and cocaine (Parker et al, 2004). The lack of effect of either capsazepine or cannabidiol per se on PPI and startle response suggests that these drugs do not directly interfere with normal sensorimotor gating in the mouse.…”
Section: Discussionmentioning
confidence: 62%